Ecological space resilience assessment of Baiyangdian Basin from the perspective of evolutionary resilience - Liang, Xinyu; Gao, Xing; Zhao, Meiran; Guo, Zhongyuan; Shen, Weining (Frontiers in Ecology and Evolution, 2023)
The structure and function of ecological spaces play a crucial role in resisting risk interference and providing ecological services. Conducting resilience assessments of ecological spaces is of great significance for maintaining ecological security. Taking the Baiyangdian Basin as the research object, based on the evaluation results of ecosystem service function importance and ecological environmental sensitivity, the ecological space importance level of the Baiyangdian Basin is divided. Based on the three basic characteristics of "resistance, adaptability, recoverability", the resilience of ecological space model was constructed by selecting ecosystem service value, landscape structure stability, ecological resilience model and coefficient. The research results show that: (1) The overall importance index of ecological space in the Baiyangdian Basin is relatively low. The non-critical area accounted for 43.00% of the total area, the general area accounted for 30.78%, and the core area accounted for 26.22%, which mainly distributed in the northern part of the study area and at the confluence of rivers. (2) The proportion of areas with extremely important ecosystem service functions in Baiyangdian Basin is 31.73%, concentrated in the central and southwestern parts of the basin. The highly sensitive ecological environment areas accounted for 21.96%, mainly distributed in high-altitude areas in the northern part of the basin and river convergence areas. (3) On the whole, the overall resilience level of the study area is not high and there is a significant difference in resilience between the north and south, with 68.60% of the regions in the low level of resilience. The area with high resilience level accounted for only 1.51%, and the highest resilience level was found at river confluence. The research results provide a theoretical basis for maintaining and improving the ecological environment of the basin, and provide a basis for implementing precise policies to optimize the ecological space of the basin.